ﺛﺮ اﻟﺒﯿﺌﺔ اﻟﺨﺎرﺟﯿﺔ ﻓﻲ ﻋﻤﻠﯿﺔ ﺻﻨﻊ ﻗﺮار‬ ‫إﻏﻼق ﻣﺸﺎرﯾﻊ اﻟﻘﻄﺎع اﻟﺼﻨﺎﻋﻲ اﻟﺨﺎص‬ ‫اﻟﺘﺠﺮﺑﺔ اﻟﻌﺮاﻗﯿﺔ )ﻟﻠﻤﺪة ‪(١٩٨٥-١٩٧٦ - د. سميرة كاظم الشماع (College of Education for Women, 2019)
Abstract The research hypothesizes is that the external Environment has the responsibility concerning decisions making and behavioral upon industrial firms. It is, Furthermore, an attempt to review the problem of closures of private industrial firms in the country, during the period (1976-1985), i.e. prior to and during the Iraqian- Iranian war. The behavioral approach of industrial geography has been adopted as a theoretical background and the statistical test has been practiced for the applied purposes. As result, the research comes out with suggestions, depending upon previous trials in the field of direction and formulation of the of the private industrial sector. The chief point among these suggestions is that the coordination of this sector with the currently changes in the world economy today is strongly required.